Nilai-Nilai Akhlak Dalam Novel Tirani Dedaunan Karya Chairul Al-Attar dan Saran Penerapannya pada Pembelajaran Sastra di SMA - Hafilda, Virra; Israhayu, Eko Sri (Ruang Kata, 2023)
This study aims to describe the form of moral values depicted by the behavior of the characters in the novel Tirani Dedaunan by Chairul Al-Attar and how the suggestions for its application in literature learning in high school. This type of research is descriptive qualitative by utilizing a literary religious approach. The data used are in the form of sentences or quotations that identify elements of religiosity in the form of moral values. The data source used is the novel Tirani Dedaunan by Chairul Al-Attar. Data collection techniques use reading techniques and note-taking techniques. The researcher used theoretical triangulation technique in the data validity technique. Data analysis was carried out based on four stages, namely data organization, data reduction, data presentation, and conclusion drawing. The result of this study is that there are four forms of moral values found in the novel Tirani Dedaunan by Chairul Al-Attar, such as morals towards God, morals towards oneself, morals towards family, and morals towards society. These moral values can be implemented in literature learning based on KD 3.14 and 4.14 of the 2013 edition of the curriculum in 2018.Keywords: morals, novel, literature learning